Tuberculosis: fasten your seat belts, we are entering a turbulence zone! - O.O. Chernenko (Civic Union "Communicable Diseases Intensive Care Association", 2022)
The article outlines the main aspects of the impact on the situation with the incidence of tuberculosis in Europe as a result of the Russian-Ukrainian war. On the basis of foreign sources, the main links of this influence are highlighted, in particular, epidemic, resource, personnel, etc. The author expresses his opinion on the problematic aspects of the health care reform in terms of controlling the incidence of tuberculosis in Ukraine, as well as on the possible steps that would allow the situation to be brought under control.